Type 1 Fimbria-Mediated Adhesion of Enteric Bacteria to Grass Roots - Haahtela, Kielo (1985)
Type 1 fimbriae of Klebsiella pneumoniae and Enterobacter agglomerans mediated bacterial adhesion to the roots of bluegrass, Poa pratensis. Purified, radiolabeled fimbriae bound to grass roots in vitro; binding was inhibited by α-methyl-d-mannoside or Fab fragments to the fimbriae. Anti-type 1 fimbriae Fab fragments and α-methyl-d-mannoside also inhibited adhesion of type 1-fimbriated bacteria to P. pratensis roots. It is proposed that associative nitrogen fixation by Klebsiella and Enterobacter strains also involves type 1 fimbriae, in addition to the type 3 fimbriae of Klebsiella spp. (T. K. Korhonen, E. Tarkka, H. Ranta, and K. Haahtela, J. Bacteriol. 155:860-865, 1983).